Analisis Kualitas Jaringan Internet pada SMK Menggunakan Metode Quality of Service - M. Septrio Rafinaldo; Iwan Iskandar; Nazruddin Safaat Harahap; Reski Mai Candra (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
One of the most common uses of Internet technology is in the field of education. The utilization of the Internet in education has long been employed by SMK Negeri 1 Tembilahan. This school utilizes internet connectivity as a tool and means to support the teaching and learning process. Therefore, the school must provide a reliable network service to ensure smooth learning experiences. This research aims to evaluate the quality of internet connectivity at SMK Negeri 1 Tembilahan using the Quality of Service (QoS) method with parameters such as throughput, delay, packet loss, and jitter. The study also analyzes the internet quality in each department of SMK Negeri 1 Tembilahan during peak and off-peak hours, involving both teachers and students as users. With a total of 1,307 users, the school utilizes an internet connection from an Indihome provider with a bandwidth of up to 300 Mbps. The test results indicate that the throughput, packet loss, delay, and jitter values are rated at index 4, categorized as "Very Good." However, it is worth noting that the throughput value for student users in the Design Communication Visual and Computer Network Engineering departments is rated at index 2, categorized as "Fair." These findings provide valuable information and insights for the school to assess the quality of internet services at SMK Negeri 1 Tembilahan in supporting teaching and learning activities. By addressing the identified issues, such as the lower throughput in specific departments, the school can take appropriate measures to enhance the internet infrastructure and improve the learning experience for students. This research serves as a valuable resource for the school administration to make informed decisions and improvements regarding the quality of internet connectivity, ultimately benefiting the teaching and learning process at SMK Negeri 1 Tembilahan